Diamond crystallization and growth in N–H enriched environment under HPHT conditions. Issue 43 (24th October 2016) - Liu, Xiaobing; Jia, Xiaopeng; Fang, Chao; Ma, Hong-An
Abstract : We report our systematic study of nitrogen and hydrogen on diamond crystallization under HPHT conditions. Our results provide new experimental evidence for the aggregation of nitrogen impurities (A- and B-centers) and formation of 3107 cm −1 center (hydrogen-related defect) during diamond growth that could provide us deeper insights into the genesis of natural diamond. Abstract : Advances in understanding the state and transformation of impurity-related defects in natural diamond have been achieved by means of high-pressure and high-temperature annealing experiments. However, the existing literature featuring complex behaviors of aggregated nitrogen and hydrogen-related defect (3107 cm −1 center) has remained controversial. Their formation mechanism during diamond crystallization is still unclear, thus further investigation is required. In this work, we have successfully synthesized a variety of high-quality diamonds containing nitrogen impurities with IaA (nitrogen pairs), IaB (group of four nitrogen atoms around a vacancy) and Ib (single-substitutional nitrogen) characteristics ranging from <1 ppm to 3380 ppm at pressures ranging from 5.0 GPa to 6.3 GPa and temperatures of 1300–1650 °C. Our results provide new experimental evidence for the aggregation of nitrogen impurities (A- and B-centers) during diamond growth. We notice that the hydrogen is easily trapped by nitrogen atoms to form nitrogen–hydrogen complexes (–NH, –NH2, –NH3 ) when the nitrogen tends to form C-centers in hydrogen-enriched environments. Additionally, we observed that the high reaction temperature and formation of A-centers during diamond growth play important roles in the formation of the 3107 cm −1 center. We believe the current results could be helpful for further understanding and constructing a clear model of impurity-related defects, and thus provide us deeper insights into the genesis of natural diamond.